2017
DOI: 10.1016/j.jcmg.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Integrating CT Myocardial Perfusion and CT-FFR in the Work-Up of Coronary Artery Disease

Abstract: CT MPI and CTA FFR both identify functionally significant CAD, with comparable accuracy. Diagnostic performance can be improved by combining the techniques. A stepwise approach, reserving CT MPI for intermediate CTA FFR results, also improves diagnostic performance while omitting nearly one-half of the population from CT MPI examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 30 publications
5
91
1
4
Order By: Relevance
“…Thus, a rest-stress-DECT-P protocol, or a CT-based FFR calculation seems to be a promising concept to improve diagnostic accuracy in a real clinical setting (12).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a rest-stress-DECT-P protocol, or a CT-based FFR calculation seems to be a promising concept to improve diagnostic accuracy in a real clinical setting (12).…”
Section: Resultsmentioning
confidence: 99%
“…2) and CT perfusion (CTP) in a stepwise manner may significantly improve diagnostic accuracy. 11 Further analysis of the CORE-320 multicentre registry data, demonstrated that results from CTA and CTP were similarly predictive of major adverse cardiac events to those of combined invasive coronary angiography and SPECT findings. 12 These studies combined with a recent meta-analysis showing largely equivocal sensitivity and specificities between PET, CMR and CTP, and with all three outperforming SPECT, 13 support a promising future for CTP.…”
Section: Coronary Artery Diseasementioning
confidence: 98%
“…To date, the validation of noninvasive FFR derivation from CT for the detection of lesion-specific ischemia has been largely restricted to comparisons with invasive FFR alone or with coronary CT angiography or coronary CT angiography-derived approaches based on image postprocessing, that is, the transluminal attenuation gradient or plaque characterization (3,61). To date, only smaller scale, preliminary evidence is available on the performance of FFR CT relative to other functional imaging tests (89,106). However, several large-scale trials are currently studying the merits of FFR CT in comparison with other invasive and noninvasive functional imaging modalities.…”
Section: Contextualization and Comparison Of Ffr Ct With Other Noninvmentioning
confidence: 99%